Demolishing Humanity through Pleasure and Pain: Reading Huxley’s Brave New World and Orwell’s 1984 Side by Side - Reimundus Raymond Fatubun (Journal of Language and Literature, 2023)
Oligarchical collectivism that supports totalitarianism silences freedom of speech, privacy, assembly, etc. both personal and communal through horrific pain or plentiful pleasure.  Authors write literary works to remind readers of this situation through novels, poems, plays, political essays, and or satire. In today's life, it seems these two ways of totalitarianism are being practiced in life singly or combined in different parts of the world. This can be seen in a number of countries where the government does this both in disguise and addressed to a certain group of members of society such as in Nigeria and in real terms such as in Nicaragua. This is also done in total for a country such as Ukraine by Russia. Two of those great anti-utopia literary works are novels that raise the issue of restrained freedom of life in Huxley's Brave New World and Orwell's 1984. These two anti-utopian novels raise the issue of the freedom of life that is confined but in different ways. Using Marxist psychoanalytic criticism, this paper discusses this issue seen in both novels by the two authors.  The focus is on how both authors show totalitarianism being practiced both personally, and in the society found in these novels – how they are treated to follow rules that confine personal and societal freedom in totalitarianism.